Espaços de experimentação no audiovisual: processos de produção no streaming - Bousso, Karina (2021)
The purpose of this research is to discuss the creative processes of audiovisual productions offered and produced by streaming platforms. When analyzing the production context of the original series of these platforms, it was possible to discuss the new models of audiovisual production, with the goal to investigate possible spaces for contemporary experimentation within the scope of television media. To characterize these productions, the study is focused on three pillars: audiovisual themes, the screenplay formats in television series and the practices for distribution and releases in streaming platforms. From the accessible documents, added to the bibliographic studies, a comparative analysis was made between several series considered relevant for the discussion – mostly from Netflix –, with the purpose of mapping the present gaps for new tests in audiovisual productions. The theoretical framework of this research is concentrated between three main lines: Firstly, we approached the theories of Salles (2008; 2011; 2017) for the definition of the production context and the better understanding of the spaces for contemporary experimentation; secondly, the study was based on the theories of Morin (2011) about cultural imprinting as well as on the research of Domenico De Masi (2007) and his contributions to the study of “creative groups”. Finally, the studies by Arlindo Machado (2019) on the quality of television programming and his definitions of genres and narrative series were important for the interpretation of the analyzed shows. Other authors dealing with the characteristics of the entertainment industry, as well as the production of content in digital media were used. As a result of this analysis, it was possible to conclude that there are spaces for testing as we focus our attention on the potential of content creation on social networks. In this case, characteristics of the production made for Instagram called @eva.stories were pointed out in order to discuss the adaptations that can be made in audiovisual productions for the greater exploration of contemporary experimentation